Institutional blockholders and corporate innovation - Guo, Bing; Hutschenreiter, Dennis C.; Pérez-Castrillo, David; Toldrà-Simats, Anna (Journal of Corporate Finance, 2026)
The previous literature finds a positive effect of institutional (relative to other investors’) ownership on firms’ innovation output . We study the impact of increases in the concentration of institutional investors’ ownership on firms’ decisions to invest in innovation and their innovation output. By reducing short-term earnings pressure, concentrated institutional investors’ ownership increases managers’ incentives to invest in R&D. However, it decreases firms’ acquisitions of external innovation due to empire-building and dilution concerns. Overall, firms’ future patents and citations decrease. Our results indicate that the previously found positive effect of institutional investors on innovation declines as the ownership of these investors becomes more concentrated. Despite that, we find that blockholder institutional ownership increases firm value. Hence, large institutional investors take measures to preserve the value of their ownership interests, even if they result in reduced innovation.